Tumor response to EGFR/BRAF/MEK co-inhibition in a patient with EGFR mutated lung adenocarcinoma developing a BRAFV600 mutation as an acquired resistance mechanism. (September 2021) - Mauclet, Charlotte; Collard, Philippe; Ghaye, Benoit; Hoton, Delphine; Nana, Frank Aboubakar
Highlights: Lung adenocarcinoma treated with osimertinib inevitably develops resistance. Resistance to osimertinib can develop through a BRAF V600 mutation. Dabrafenib, trametinib and osimertinib triple therapy can offer sustained response. Triple therapy could be more efficient than dabrafenib plus trametinib. Abstract: EGFR-mutant adenocarcinomas represent 12% of unselected lung adenocarcinomas and 44% of never smoker adenocarcinomas in the Caucasian population. Activating mutations like exon19 deletion or exon21 Leu858Arg point mutations are predictive of tumor response to EGFR tyrosine kinase inhibitors. Unfortunately, acquired resistance inevitably occurs by the development of novel EGFR mutations, mutations in other genes, gene amplification, gene fusion or tumor transformation. The management of tumors presenting multiple targetable mutations is unclear. We present the case of a patient developing a BRAF V600 mutation as acquired resistance mechanism to osimertinib, who responded favorably to the combination of dabrafenib, trametinib and osimertinib.